Development of an automated, high-throughput SARS-CoV-2 neutralization assay based on a pseudotyped virus using a vesicular stomatitis virus (VSV) vector - Ziteng Liang; Xi Wu; Jiajing Wu; Shuo Liu; Jincheng Tong; Tao Li; Yuanling Yu; Li Zhang; Chenyan Zhao; Qiong Lu; Haiyang Qin; Jianhui Nie; et al. (Emerging Microbes and Infections)
The global outbreak of COVID-19 has caused a severe threat to human health; therefore, simple, high-throughput neutralization assays are desirable for developing vaccines and drugs against COVID-19. In this study, a high-titre SARS-CoV-2 pseudovirus was successfully packaged by truncating the C-terminus of the SARS-CoV-2 spike protein by 21 amino acids and infecting 293 T cells that had been stably transfected with the angiotensin-converting enzyme 2 (ACE2) receptor and furin (named AF cells), to establish a simple, high-throughput, and automated 384-well plate neutralization assay. The method was optimized for cell amount, virus inoculation, incubation time, and detection time. The automated assay showed good sensitivity, accuracy, reproducibility, Z’ factor, and a good correlation with the live virus neutralization assay. The high-throughput approach would make it available for the SARS-CoV-2 neutralization test in large-scale clinical trials and seroepidemiological surveys which would aid the accelerated vaccine development and evaluation.